Anattempt to rebuild the world "in the American way" - A. D. Bogaturov (Vestnik MGIMO-Universiteta, 2021)
Trump’s foreign policy was controversial, resulting in division into its supporters and adversaries both at national and international levels. Donald Trump managed to be flexible in relations with the Legislative, ignoring the democratic majority in the House of Representatives. However, it was possible only before the Covid-19 pandemic. Donald Trump’s foreign policy prioritized American capital that determined US relations with the EU, Canada, and Latin America. As for relations with Russia, they were defined by the Ukrainian crisis. Disarmament is still a cornerstone in Russian American relations. The US has complicated relations with countries in Latin America, the Middle East, and the Persian Gulf despite all efforts. The UN’s reform and the Security Council, where the three great powers primarily make decisions, are still questioned. The US divides Europe into three parts; Western Europe, Eastern Europe, and Russia with Belarus. These Europes have different views on US foreign policy. Republican administration aimed at the expansion of the national power and provision of global leadership. However, the implementation methods were questionable and led to some unpleasant consequences for the US allies. Some of them decided to wait, some prepared for the worst, some tried to adapt to Trump’s policy since it reflected the long-term changes of the US standing in the world regardless of the party or the president. As a result, such policy led to the defeat of the Republicans and brought Joe Biden to power.